Chemically reactive hybrid nanofluid flow past a Riga plate with nonlinear thermal radiation and a variable heat source/sink - Algehyne, Ebrahem A.; Lone, Showkat Ahmad; Raizah, Zehba; Eldin, Sayed M.; Saeed, Anwar; Galal, Ahmed M. (Frontiers in Materials, 2023)
The suspension of nanoparticles in base liquids has been found in extensive applications in various industrial processes like nanomedicines, cooling of microsystems, and energy conversion. Owing to its important applications an attempt has made in this article to investigate the hybrid nanofluid flow over a three dimensional stretching surface. The fluid is influenced by thermal radiation, chemical reaction and variable thermal source/sink. The set of equations that administered the fluid behavior has been transformed to dimensionless form by suitable set of similarity transformations. Which are further solved by the homotopy analysis method (HAM). After detail insight of the problem, it came to know that upsurge in ratio parameter; the hybrid nanofluid velocity along primary direction is declined, while secondary direction is grown up. Temperature characteristic has augmented with greater values of nonlinear thermal radiations and source sink factors. Growth in chemically reactive factor and Schmidt number has an adverse effect on concentration profile of the hybrid nanofluid flow. A comparative analysis among the current results and those established in literature has been conducted and found a close agreement with those published results. It has noticed that temperature and concentration are augmenting quickly for hybrid nanofluid than nanofluids.